AB1040 The incidence of previously undiagnosed conditions in patients attending fracture liaison service. (23rd January 2014) - Abdulkader, R.; Dharmapalaiah, C.; Stephenson, S.; Clunie, G.
Abstract : Background: The role of a fracture liaison service (FLS) is significant not only in secondary fracture prevention but also in the identification of medical conditions adversely affecting bone metabolism. Addressing these conditions aims at improving bone health and general wellbeing. Objectives: We have reviewed the incidence of new medical conditions identified through routine investigations in patients aged 50-80y seen in The FLS in our unit (fracture cases >80y not included). Methods: All patients who attend The FLS clinic (age 50-80y) have an assessment including review of past history, DXA scan, blood tests U&Es, bone profile, PTH, thyroid function test, Vitamin D, CRP. Additionally in patients >70y old, serum protein electrophoresis is checked. Male patients are tested for hypogonadism. We retrospectively reviewed patients attending FLS clinic who were identified with a previously-undisclosed medical condition between November 2008 and October 2011.We reviewed FLS and any subsequent clinic letters and the Hospital laboratory database. We did not include new diagnoses of vitamin D deficiency or cases where increased falls tendency was identified and investigated. Results: Over this 3-year period, 2876 patients (aged 50-80) attended the FLS clinic. Review resulted in the identification of 74 cases (2.5%) of previously undiagnosed medical conditions relevant to poor bone health. Of these cases 28 (1%) were found to have primary hyperparathyroidism (PHPT) and 5 patients were found to have paraproteinemia (3 cases of monoclonal gammopathy of unknown significance and 2 still under investigation). Hypogonadism was identified in 19 men (15 primary hypogonadism, 4 secondary [2 with hyperprolactinemia]). Other cases identified included: hyperthyroidism (4), celiac disease (1), hypothyroidism (11), inflammatory arthritis (2) and chronic kidney disease 3-5 (2). In 2 patients, review was inconclusive owing to loss of follow-up; one may have had PHPT and a male patient with possible hypogonadism. Conclusions: In our FLS, routine and simple screening disclosed new medical conditions, relevant to bone health in 2.5% fracture cases (age 50-80y). Notably the incidence of PHPT detected our fracture patients aged 50-80y is at least 10 times its incidence in the general population (1% vs 0.1%).We suggest that 1% is an underestimate in fracture patients overall though as screening was not designed to capture any new PHPT in those >80y. Disclosure of Interest: None Declared